COMMUNICATION BETWEEN PERSONAL TEACHERS WITH CLASS 5 STUDENTS AT SDN PETAMBURAN 01 MORNING IN MOTIVATING LEARNING - Rezki Kurniawan (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2020)
The background of this research is the phenomena that make students become lazy to learn because the factors affecting today's modern era. For it was in need of interpersonal communication research teachers with students in motivating learning. The theory used is Interpersonal communication theory, motivating theory, and group communication theory. The method of this research is to use a descriptive qualitative. Data collection techniques by conducting structured interviews and observations. The purpose of this research is to find out how the teacher role in order for students to be open in learning and how can teachers motivate students in stimulating learning. Summary of the research is now pretty good teachers motivate students while in the classroom.